Indentation size effect in steels with different carbon contents and microstructures. Issue 3 (11th February 2023) - Sarangi, Soumya Sourav; Lavakumar, Avala; Singh, Prince Kumar; Katiyar, Prvan Kumar; Ray, Ranjit Kumar
Abstract : Indentation Size Effect (ISE) in steels having a wide spectrum of carbon (C) concentrations (wt-%) 0.002 (interstitial-free), 0.07 (microalloyed), 0.19 (low carbon), 0.32 (medium carbon), and 0.7 (high carbon), and microstructures were investigated using Vickers micro-hardness tester. A decrease in micro-hardness with increasing load, i.e. ISE, is observed in all the samples except microalloyed steel. The empirical relations, such as the Nix and Gao model, Minimum Resistance model, and Proportional Specimen Resistance (PSR) model, were used to determine the load-independent or true hardness values. Nix and Gao model was adopted to determine the plastically deformed zone (PDZ) size under the indenter and subsequently correlated with ISE in the materials. It is observed that ISE is absent when the PDZ size becomes comparable to or larger than the grain size of the material.